Divergent effects of entomopathogenic fungi and medicinal mushroom species on Drosophila melanogaster lifespan - Md M. H. Nafis; Amran A. Q. A. Al-Shaarani; Mohammed H. M. Muafa; Yiwen Wang; Chunying Deng; Yusufjon Gafforov; Lorenzo Pecoraro (All Life)
We tested the effect of entomogenous fungi isolated from the Coleoptera species Ophrida xanthospilota and of the medicinal mushroom Lentinula edodes on the lifespan of Drosophila melanogaster. All the four analyzed strains of entomogenous fungi showed pathogenicity to D. melanogaster by causing 100% mortality of fruit flies within 20 culture days. The shortest lifespan was recorded in flies treated with Fusarium verticillioides (15 days). On the contrary, L. edodes showed a remarkable lifespan-extending effect on the model organism, with fruit fly individuals surviving for 55 culture days. Fungal growth was microscopically observed on the bodies of dead fruit flies treated with the four entomogenous fungal species, confirming that the tested fungi were responsible for the mortality of the model insects. Our findings showed that the four fungal species previously found on the body of Coleoptera individuals are entomopathogenic and could be exploited in agriculture applications for the biocontrol of noxious pests. The significant lifespan extending effect on Drosophila produced by the analyzed L. edodes strain could represent very important experimental evidence of the anti-aging and lifespan prolonging effects of this medicinal mushroom species.